Severe Vitamin D Deficiency in Youth with Autism Spectrum Disorder During the COVID-19 Pandemic. Issue 8 (15th October 2022) - Ganta, Avani; Pillai, Sabitha S.; Fredette, Meghan E.; Topor, Lisa Swartz
ABSTRACT: Background: Decrease in sunlight exposure during periods of social distancing during the COVID-19 pandemic increased the risk of severe manifestations of vitamin D deficiency (VDD) in a particular "high-risk" population. Our objective was to highlight the importance of vitamin D screening in youth with autism spectrum disorder (ASD) and restrictive eating. Case Presentation: We describe 3 adolescent male patients with ASD who developed severe manifestations of VDD and hypocalcemia in late 2020 during the COVID-19 pandemic. All spent less time outdoors than in prior years because of isolation at home during the pandemic. Presenting symptoms included seizures and atraumatic fractures. All 3 were found to have hypocalcemia and severe VDD. Limited sun exposure because of isolation indoors during the COVID-19 pandemic was a likely contributing factor to the severity of VDD. All 3 were treated with intravenous calcium acutely, followed by oral calcium and vitamin D. Laboratory tests performed post-treatment showed biochemical resolution of hypocalcemia and VDD. Conclusion: These cases highlight the importance of screening "at-risk" youth for VDD. Clinicians should be cognizant that children and adolescents with ASD and restricted eating can have severe manifestations of hypocalcemia and VDD. Decreased sun exposure because of isolating indoors during the COVID-19 pandemic increased their risk for this.